Polyvinylidene fluoride nanofibers with embedded Li6.4La3Zr1.4Ta0.6O12 fillers modified polymer electrolytes for high-capacity and long-life all-solid-state lithium metal batteries. (10th November 2020) - Gao, Lu; Li, Jianxin; Ju, Jingge; Cheng, Bowen; Kang, Weimin; Deng, Nanping
Abstract: Solid polymer electrolytes replacing traditional liquid electrolytes are considered as an important strategy for developing lithium metal batteries with high safety and energy density. However, poor ionic conductivity and weak mechanical performances have greatly limited the development of solid polymer electrolytes. Here, we dispersed inorganic ceramic particles Li6 · 4 La3 Zr1 · 4 Ta0 · 6 O12 (LLZTO) in the polyvinylidene fluoride (PVDF) electrospun nanofibers and then introduced them into polyethylene oxide (PEO) polymers to prepare composite electrolytes. The PVDF nanofibers with embedded LLZTO fillers can simultaneously reduce the crystallinity of the PEO polymer and provide a strong framework support for the composite electrolyte, thereby promoting the transmission of lithium ions and improving the lithium dendrite growth inhibition ability of the composite electrolyte. In addition, the uniform dispersion of garnet-type LLZTO active ceramic filler in the PVDF nanofiber membrane can further optimize the migration path of lithium ions. More importantly, the dehydrofluorination of PVDF due to the introduction of LLZTO can enhance the interaction among PVDF, LLZTO and lithium salts, which promotes dissociation of the lithium salt. The ionic conductivity of the composite electrolyte is as high as 9.30 × 10 −4 S cm −1 at 50 °C, and the voltage of Li/Li symmetrical battery would not change significantly during 1200 h at 0.3 mA cm −2 . Additionally, the composite electrolytes exhibit good electrochemical stability with the capacity retention rate of 96% under 1 C after 500 cycles. These results provide a strategy for the development of next-generation high-safety all-solid-state lithium metal batteries. Graphical abstract: An all-solid-state composite electrolyte is synthesized, which has superior ion transmission characteristics, mechanical strength and flexibility, bringing excellent long-cycle stability to Li/Li symmetric battery and Li/LiFePO4 battery. Image 1 Highlights: An all-solid-state composite polymer electrolyte are successfully prepared. Composite polymer electrolyte exhibits excellent mechanical strength and flexibility. Li/Li batteries and Li/LiFePO4 batteries assembled with the composite electrolytes have superior long-cycle stability.